Initial formation of rural education teachers: the experience of PRONERA/UERN in biographical narratives - Aguiar, Ana Lúcia Oliveira; Medeiros, Emerson Augusto de (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2018)
The article on screen presents reflections built in a argumentative study on the initial formation of education teachers of the field based on the experience of the National Program of Education in agrarian reform – PRONERA, of the University of the state of Rio Big North-UERN. In methodological parameters, we made use of the qualitative approach of research and interviews of life stories with three graduates of the pedagogy course, the initial education project of Terra-UERN. We believe that in the experience of UERN, PRONERA has achieved one of the main challenges in the formation of teachers of the field education in the country, which is: to develop formative processes that relate the university training of faculty members of the Basic education with the knowledge, history and memory, life experiences and cultural practices of the peoples of the countryside.